2007
DOI: 10.1289/ehp.10318
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Air Pollution, Oxidative Stress Genes, and Heart Rate Variability in an Elderly Cohort

Abstract: Background and objectivesWe have previously shown that reduced defenses against oxidative stress due to glutathione S-transferase M1 (GSTM1) deletion modify the effects of PM2.5 (fine-particulate air pollution of < 2.5 μm in aerodynamic diameter) on heart rate variability (HRV) in a cross-sectional analysis of the Normative Aging Study, an elderly cohort. We have extended this to include a longitudinal analysis with more subjects and examination of the GT short tandem repeat polymorphism in the heme oxygenase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(131 citation statements)
references
References 46 publications
(68 reference statements)
6
121
1
3
Order By: Relevance
“…207,243,244 Additional findings suggest protective effects of statins, dietary antioxidants, and B vitamins, as well as omega-3 polyunsaturated fatty acids. 205,207,215,243,244 These results suggest that pathways that reduce endogenous oxidative stress have a protective effect that mitigates reductions in HRV due to ambient PM exposure.…”
Section: Heart Rate Variabilitymentioning
confidence: 80%
“…207,243,244 Additional findings suggest protective effects of statins, dietary antioxidants, and B vitamins, as well as omega-3 polyunsaturated fatty acids. 205,207,215,243,244 These results suggest that pathways that reduce endogenous oxidative stress have a protective effect that mitigates reductions in HRV due to ambient PM exposure.…”
Section: Heart Rate Variabilitymentioning
confidence: 80%
“…10 Others found an association of GSTM1 0/0 with heart failure. 11,12 Black carbon and particulate matter exposure was shown to be associated with increased intracellular and vascular cell adhesion molecules, which promoted atherosclerosis; this association was modified by the presence of the GSTM1 polymorphism. 13 GSTP1 and GSTM1 polymorphisms have been associated with the biomarker of oxidative DNA damage, 8-hydroxy-2'-deoxyguanosine and increased susceptibility to smoking-related CAD.…”
mentioning
confidence: 99%
“…The results in human particulate air pollution exposure studies have been more mixed. Two studies in an older cohort in Mexico with metabolic syndrome showed attenuation of the acute PM effect on heart rate variability after long-term supplementation with fish oil (33,34). In a controlled exposure experiment to ozone, Samet and colleagues (35) showed a smaller decrement in lung function after supplementation with a cocktail of AA, a-tocopherol, and vegetables.…”
Section: Antioxidant Pretreatmentmentioning
confidence: 99%